2016
DOI: 10.1186/s12879-016-1938-8
|View full text |Cite
|
Sign up to set email alerts
|

The COX- inhibitor indomethacin reduces Th1 effector and T regulatory cells in vitro in Mycobacterium tuberculosis infection

Abstract: BackgroundTuberculosis (TB) causes a major burden on global health with long and cumbersome TB treatment regimens. Host-directed immune modulating therapies have been suggested as adjunctive treatment to TB antibiotics. Upregulated cyclooxygenase-2 (COX-2)-prostaglandin E2 (PGE2) signaling pathway may cause a dysfunctional immune response that favors survival and replication of Mycobacterium tuberculosis (Mtb).MethodsBlood samples were obtained from patients with latent TB (n = 9) and active TB (n = 33) before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 66 publications
0
28
0
1
Order By: Relevance
“…Selective COX-2 inhibitors decrease unproductive inflammation and improve survival in murine TB by direct anti-mycobacterial activity. [101][102] COX2-inhibition is however, also associated with cell necrosis, which favours Mtb survival. 103 Zileuton, a 5-LOX inhibitor, approved for use in asthma, increases PGE2 and inhibits leukotrienes to limit type I IFN-mediated lung pathology.…”
Section: Eicosanoid Modulatorsmentioning
confidence: 99%
“…Selective COX-2 inhibitors decrease unproductive inflammation and improve survival in murine TB by direct anti-mycobacterial activity. [101][102] COX2-inhibition is however, also associated with cell necrosis, which favours Mtb survival. 103 Zileuton, a 5-LOX inhibitor, approved for use in asthma, increases PGE2 and inhibits leukotrienes to limit type I IFN-mediated lung pathology.…”
Section: Eicosanoid Modulatorsmentioning
confidence: 99%
“…We also hypothesised that celecoxib might affect growth in the WBA assay through the direct T-cell immunomodulatory effects of COX inhibition 15 . The ex vivo WBA paradigm has the potential advantage over in vitro assays of evaluating the integration of effects of anti-mycobacterial drugs with host immune responses, both of which have been established independently in healthy volunteers using the WBA model 19 , 22 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Dosing TB-infected murine models with COX inhibitors reduces lung infiltrates, lowers bacillary loads and improves survival 7 , 11 14 . COX suppression also inhibits immune activation of T cells by Mycobacterium tuberculosis (Mtb) 15 . In addition, synergy between anti-tuberculosis drugs and COX inhibition (pyrazinamide with ibuprofen 16 and streptomycin with diclofenac 12 ) has been seen in mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, Tonby et al reported that the use of this inhibitor decreases the proliferation and cytokine secretion of mycobacterial antigen stimulated lymphocytes from TB patients. However, these observations could be linked to a direct inhibitory effect of indomethacin on the activation of the NF-κB pathway 21 .…”
Section: Discussionmentioning
confidence: 99%